Retention of molars after root-resective therapy: a retrospective evaluation of up to 30 years - Derks, Hermann; Pfefferle, Thorsten; Eickholz, Peter; Dannewitz, Bettina (Clinical oral investigations, 2018)
Objectives Long-term retention of teeth and especially molars in function is the ultimate goal of periodontal therapy. Rootresective therapy is a treatment option for molars with advanced furcation involvement, which has been questioned because of the heterogenous success rates published in literature. This study aimed to evaluate long-term results of rootresective treatment over a period of up to 30 years.